2019
DOI: 10.1002/ange.201902779
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Synthesis of α‐Trifluoromethyl Carboxylic Acids and Esters through Fluorocarboxylation of gem‐Difluoroalkenes

Abstract: Afacile synthetic procedure for the preparation of atrifluoromethyl carboxylic acids and esters was achieved through multicomponent coupling reactions between gemdifluoroalkenes,c esium fluoride,a nd carbon dioxide.T he products were generated in moderate to excellent yields,a nd the synthetic utility of this method was demonstrated through the preparation of trifluoromethylated versions of popular nonsteroidal anti-inflammatory drugs (NSAIDs). Scheme 1. Synthesis of a-trifluoromethyl carboxylic acids.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…The previously formed 4CzPEBN • – ( E 1/2 (P/P • – ) = −1.69 V vs SCE, Figure S1 ) should be able to reduce the benzylic radical ( E 1/2 red = −1.60 V vs SCE for the phenylethyl radical) 17 to accomplish the photoredox catalytic cycle and afford the carbanion of ethylbenzene. It is well-known that this anion can be readily captured by CO 2 , 18 generating the final product after protonation. Overall, CO 2 formally inserts into the benzylic C–H bond without the addition of any sacrificial reagent ( Scheme 3 ).…”
mentioning
confidence: 99%
“…The previously formed 4CzPEBN • – ( E 1/2 (P/P • – ) = −1.69 V vs SCE, Figure S1 ) should be able to reduce the benzylic radical ( E 1/2 red = −1.60 V vs SCE for the phenylethyl radical) 17 to accomplish the photoredox catalytic cycle and afford the carbanion of ethylbenzene. It is well-known that this anion can be readily captured by CO 2 , 18 generating the final product after protonation. Overall, CO 2 formally inserts into the benzylic C–H bond without the addition of any sacrificial reagent ( Scheme 3 ).…”
mentioning
confidence: 99%
“…In 2019, Kobayashi and co‐workers developed a simple and straightforward procedure for the fluorocarboxylation of gem‐ difluoroalkenes 63 . [ 27 ] This catalyst‐ and additive‐free protocol, proceeding in the presence of nucleophilic CsF and CO 2 , was facilitated by the presence of polar solvents such as DMSO (Figure 20). Although providing useful yields at atmospheric pressure of CO 2 , the reaction efficiency became excellent at 20 atm.…”
Section: Metal/base‐promoted Alkene Carboxylative Functionalizations With Co2mentioning
confidence: 99%
“…Bonnet–Delpon and co-workers already demonstrated that gem -difluoroalkene-derivatized artemisinins exhibit prolonged in vivo antimalarial activity through replacement of the carbonyl group 5 . Moreover, gem -difluoroalkenes can be transformed to various organofluorine motifs 6 , 7 such as trifluoromethyl 8 10 , difluoromethyl 11 14 , monofluoroalkenyl 15 18 , and difluoromethylenyl 19 , 20 groups for late-stage functionalization. Conventionally, Wittig- or Horner-Wadsworth-Emmons-type olefination and S N 2’ reactions of vinyl trifluoromethyl compounds are widely employed to construct the gem -difluoroalkene moiety 7 , 21 , 22 .…”
Section: Introductionmentioning
confidence: 99%